THE INFLUENCE OF TASK-BASED LANGUAGE TEACHING IN EFL READING CLASSROOM - Doris Sukma; Yenni Rozimela; Ratmanida -; Muhammad Indra Gunawan (INOVISH JOURNAL, 2022)
This study is set out to investigate the influence of task-based language teaching implementation to teach reading comprehension to EFL students. It involved the first-year students of SMAN 3 Padang as research population. They were consisted of eight classes. Two groups were assigned as experimental and control class. There were 36 students in each class. The groups were taught by using different teaching instruction. Experimental group were taught by using task-based language teaching while control group were taught by using conventional teaching. After several treatments, these groups were given reading comprehension test in order to see their comprehension quality toward reading text. The test was in form of short answer response and consisted of 26 valid and reliable items. As prerequisite analysis, normality and homogeneity testing were conducted in order to analyze the result of the test. Subsequently, independent sample t-test was conducted in order to test the research hypothesis. Based on the result of analysis, it was found that tobtained (3.503) was higher than ttable (1.669). It designates that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Otherwise speaking, task-based language teaching gives positive influence toward students’ reading comprehension